The Neglected Tropical Disease Non-Governmental Organization Network: The role of a global health network in an evolving global health landscape. - Girija Sankar; Arielle Dolegui; Jemish Acharya (PLOS Global Public Health)
The Neglected Tropical Diseases NGO Network (NNN) was established in 2009 to bring together non-governmental organizations (NGOs) working towards the control and elimination of neglected tropical diseases (NTDs). In response to the evolving landscape of global health and the increasing focus on equity, the NNN conducted a membership analysis in 2021. This analysis aimed to assess the network's composition and connectivity, revealing significant insights into its current structure and areas for improvement. Key findings from the analysis include the following: a majority of NNN members were based in high-income countries (HICs); 40% of the member organizations concentrated on a single NTD; the African region had nearly twice the number of member organizations supporting interventions in the region compared to other regions; and, members from HICs tend to be better networked within the NNN. These findings highlight the need for the NNN to enhance its inclusivity and representation, ensuring that voices from endemic countries are more prominently integrated into the network. By aligning with the NTD Road Map 2021-2030, the NNN aims to address these disparities and strengthen its commitment to global health equity. This analysis serves as a call to action for other global health networks to undertake similar self-assessments. Through transparency and critical reflection, the pursuit of global health equity can be advanced, ensuring that all regions and diseases receive appropriate attention and resources.